2022
DOI: 10.1016/j.sjbs.2021.08.078
|View full text |Cite
|
Sign up to set email alerts
|

A possible theranostic approach of chitosan-coated iron oxide nanoparticles against human colorectal carcinoma (HCT-116) cell line

Abstract: Iron oxides have become increasingly popular for their use as a diagnostic and therapeutic tool in oncology. This study aimed to improve pharmacological valuable of Fe 3 O 4 , which may be use to diagnosis colorectal cancers (CRC). Here, we have developed chitosan (CS) coated Fe 3 O 4 through a cost-effective procedure. First, we determined the characterization of OA-C-Fe 3 O 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 52 publications
(52 reference statements)
1
5
0
Order By: Relevance
“…Similarly, MRI results demonstrated the increased lesion localization and tumor affinity of Apt-PEG-Au-NPs@5-FU in comparison with PEG-Au-NPs@5-FU after 12 h. These results support the notion that targeted nanocarriers can be used as a preferred theranostic platform for effective CRC inhibition. This finding is consistent with the results reported by Alkahtane et al which illustrated that chitosan coated Fe 3 O 4 nanohybrid enhanced MRI contrast ability for CRC therapy (Alkahtane et al, 2022). Moreover, Zou et al reported that MUC1-SPIONs as a targeted construct can effectively improve pancreatic tumor-targeting as confirmed by both in vitro and in vivo MRI studies (Zou et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, MRI results demonstrated the increased lesion localization and tumor affinity of Apt-PEG-Au-NPs@5-FU in comparison with PEG-Au-NPs@5-FU after 12 h. These results support the notion that targeted nanocarriers can be used as a preferred theranostic platform for effective CRC inhibition. This finding is consistent with the results reported by Alkahtane et al which illustrated that chitosan coated Fe 3 O 4 nanohybrid enhanced MRI contrast ability for CRC therapy (Alkahtane et al, 2022). Moreover, Zou et al reported that MUC1-SPIONs as a targeted construct can effectively improve pancreatic tumor-targeting as confirmed by both in vitro and in vivo MRI studies (Zou et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…T98G and LN229 cells were cultured in DMEM, which was supplemented with 10% FBS and 1% PSN antibiotic under humidified conditions (5% CO 2 ). The detailed procedure of cell culture and MTT assay adapted to the standard methods and practices [ 71 ], was also implemented in our previous work [ 72 , 73 ]. Here, the concentrations of Curcumin were maintained at 0–25 µM for the treatment of the glioblastoma cell line for 24 h.…”
Section: Methodsmentioning
confidence: 99%
“…Further, Gholipour et al developed a 68 Ga-dextran complex (GaD) for dual-modality PET/MRI imaging. The efficacy of the designed complex was tested under both acidic and alkaline conditions.…”
Section: Polysaccharide-based Theranosticsmentioning
confidence: 99%
“…213 Even though the small amounts of radiopharmaceuticals can provide activities sufficient for acquisition of images, a stable chelation is required in the case of metallic tracers to ensure their safe clinical application. For example, complexation of a common PET radioisotope 68 Ga 3+ by suitable small-molecular ligands (DOTA/NOTA) can prevent its binding to transferrin in vivo as the result of mimicking Fe 3+ . 214 For some cations with a more complicated coordination core, such as a positron emitter 89 Zr 4+ (t 1/2 = 78.4h), the classic coordination yields a complex whose stability is not sufficient to endure the long exposure to the in vivo environment.…”
Section: Toxicity Assessmentmentioning
confidence: 99%